Improving Undergraduate Epidemiology Education: An Example Using Instructional Teams. Issue 2 (18th August 2020) - Brown, Heidi E; Cox, Jonathan
Abstract: Epidemiology is a core component of the undergraduate public health curriculum and a critical component of a healthy community and a comprehensive education. Evidence-based, collaborative instructional practices improve student success, reach diverse student populations, and improve learning outcomes. Here we describe the pedagogical approach of an instructional team with which we observed an 18% greater learning gain (95% confidence interval: 6.5, 29.5; t  = −3.08; P  = 0.002), based on pre-/posttesting in a large (approximately 120 students) undergraduate course, than with the prior course offering. There were no differences in DEW rates (defined as receiving a grade of D (scoring 60%–69%) or E (scoring <60%) or withdrawing (W)) between the 2 offerings, but the ratio of "A" to "B" grades was higher (by approximately 10%) after deployment of the instructional team (Pearson's χ 2 (1 degree of freedom) = 4.17, P  = 0.041). In addition, students reported greater satisfaction with the course deploying an instructional team (80.4% positive sentiment in course evaluation comments compared with 76.1% in the prior offering). As students and faculty become more familiar with effective evidence-based instructional practices, improvements in student learning can be achieved and the goal of creating an educated citizenry ready to build a healthy society will be more attainable.